Answer:
Option C.
Explanation:
In this question we will convert the equation into vertex form then find the axis of symmetry
(A) y = x² + 2x
y = x² + 2x + 1 - 1
= (x+1)² - 1
Vertex will be ( -1,-1 ) and axis of symmetry is x = -1
(B) y = x² - 16x + 58
y = x² - 16x + 64 - 6
y = ( x-8 )² - 6
Vertex is (8, -6)and axis of symmetry x = 8
(C) y = x² + 2
y = ( x - 0)² + 2
Vertex will be (0, 2) and axis of symmetry x = 0
(D) y = x² - 4x + 2
= x² - 4x + 2 + 2 - 2
y = ( x-2 )² -2 vertex is (2, -2) and axis of symmetry x = 2
Option C is the answer.